Evolution of Statistic Moments of 2D-Distributions of Biological Liquid Crystal Net Mueller Matrix Elements in the Process of Their Birefringent Structure Changes. (9th May 2010) - Ushenko, A. G.; Misevich, I. Z.; Istratiy, V.; Bachyns'ka, I.; Peresunko, A. P.; Numan, Omar Kamal; Moiysuk, T. G.
Abstract : This research is aimed to investigate the reliability of Mueller-matrix differentiation of birefringence change of optically thick layers of biological liquid crystals at the early stages of the change in their physiological state. This is performed by measuring the set of skewness and kurtosis values of Mueller matrix image of the phase elementM 44 in various points of the object under investigation.